Preschool-Aged Children’s Use of Directive Acts: A Case Study in Bina Buah Hati Preschool, Yogyakarta - Sudartinah, Titik (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2023)
Preschool-aged children start to use various types of speech acts, one of which is directive acts. This article discusses the use of directive acts by preschool-aged children, especially related to their types and fulfillment of the felicity conditions determining the success of the directive acts. The study was conducted by utilizing qualitative and quantitative data, involving 11 preschool-aged children in Bina Buah Hati Preschool, Yogyakarta. The results show that preschool-aged children mainly use the directive act of questioning, addressed to both their peers and teacher. The questions are intended to enrich their knowledge of the world around them. In addition to questioning, the directive acts are also used to request, command, invite, prohibit, and suggest. Meanwhile, related to the felicity conditions of their directive acts, it is observed that preschool-aged children have been able to meet the overall felicity conditions so that their directive acts can be perceived perfectly by their interlocutors. Aspects of power and control of the interlocutors have begun to be well-understood, so they already have the awareness to adjust the types of directive acts against the background of the interlocutors. In addition, seeds of politeness have begun to be seen through their use of directive acts.